2021
DOI: 10.21037/atm-21-4863
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of mechanisms of ferroptosis in cancer: new challenges and opportunities

Abstract: Objective: This article reviews the specific mechanism of ferroptosis in cancer and introduces in detail the opportunities and challenges of ferroptosis-based cancer therapy, aiming to provide a new research direction for tumor therapy.Background: Ferroptosis is a newly discovered programmed non-apoptotic form of cell death. Involving changes in metabolic processes and the accumulation of peroxidation caused by factors such as drugs or genes which destruct the cell membrane structure, this kind of cell death h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…SLC7A11 or Xct is a key component of the cystine/glutamate antiporter system that plays a crucial role in cellular antioxidant defenses and leads to ferroptosis in cancer cells . The primary function of the Xc-transporter is to import cystine, by providing cystine, which plays a crucial role in maintaining cellular redox balance and protecting cells from oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…SLC7A11 or Xct is a key component of the cystine/glutamate antiporter system that plays a crucial role in cellular antioxidant defenses and leads to ferroptosis in cancer cells . The primary function of the Xc-transporter is to import cystine, by providing cystine, which plays a crucial role in maintaining cellular redox balance and protecting cells from oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis shows unique morphological characteristics, such as mitochondrial atrophy and increased mitochondrial membrane density. The physiological function of ferroptosis is lacking and remains to be discovered, and in recent years, much effort has focused on investigating the potential mechanism of ferroptosis (12)(13)(14). The influencing factors of ferroptosis include iron, lipid reactive oxygen species, and glutathione peroxidase 4 (GPX4).…”
Section: Discussionmentioning
confidence: 99%
“…General characteristics of ferroptosis include moderate condensation of chromatin, ruptured mitochondrial outer membrane, mitochondrial atrophy, cytoplasmic swelling, and loss of plasma membrane integrity [ 94 ]. On the other hand, typical biochemical characteristics of ferroptosis include GPX4 inactivation, GSH depletion, and cystine deficiency [ 95 ]. It has been demonstrated that ferroptosis plays a role in neurodegeneration [ 96 , 97 , 98 ].…”
Section: Mechanisms Of Apoptosismentioning
confidence: 99%